Sistema de costos por órdenes de producción y su rentabilidad en la casa deportiva JS, Cantón La Maná, provincia de Cotopaxi periodo 2022. - Párraga Molina, Melissa Elizabeth (2023)
The research arises due to the absence of determination of the real costs involved in the production process, this aspect permitted to propose a system of costs by production orders that provides reliable information on the incurred costs in the stages of the manufacture of sports and school uniforms. The research is focused on determining the costs by production orders and the profitability at Casa Deportiva JS. For the development of the research, quantitative and qualitative research was used through an interview to the owner to obtain data about costs and profit margins based on the production process, thus, flowcharts were developed to identify the production processes of sports and school uniforms. Moreover, an observation sheet was applied to collect relevant data about the current situation of the company at the beginning of the research. The application of this system facilitated the control of costs and optimized processes, so reflecting positive values for the company. It allowed to know the real values that are generated in the production of the clothes that are made in the company. The project ended with the preparation of the statement of costs of manufactured goods, income statement, and the application of the respective financial and profitability indicators which represented vital information for the company and reflecting a profit margin of 14.32%. It was demonstrated that the company generates this percentage of profit for each income it has, being this fact a fundamental aspect in terms of development and growth for the entity.